A Large Temperature Difference Thermal Substation (LTDTS) with Electric Heat Pump and Thermal Storage Tank. Issue 1 (February 2021) - Sun, Jian; Ma, Shicai; Huo, Cheng; Ge, Zhihua; Zhou, Shaoxiang
Abstract: A new thermal substation named LTDTS is presented, which could reduce the return water temperature of primary pipeline to below 30 °C. The capacity of an existing heating pipe could be enlarged by more than 50% without changing its flow rate. The LTDTS with single-stage or two-stage heat pump is experimented, which is compared with simulation results. The LTDTS is recommended for large district heating systems due to advantages of reducing the pipe investment and recovering industrial waste heat for lower energy consumption of heating.